Factors Related To Breast Self-Examination (Sadari) In Women Of Fertile Age In Ujong Patihah Village, Kuala District, Nagan Raya Regency - Mutiana, Mutiana; Sari, Fatimah; Ba'diah, Atik (International Journal of Health Sciences, 2024)
The Aceh Health Service recorded that the number of cancer sufferers reached 1,318 people throughout 2022. This number is based on Community Health Center-based Non-Communicable Disease (NCD) Surveillance. The most cancer cases in Indonesia are breast cancer. The number of breast cancer survivors reached 1,117 people. While the second position is cervical cancer. The high incidence of breast cancer is caused by one of the reasons being the lack of awareness in women to do early detection of breasts if they experience abnormalities such as lumps. The research method is cross -sectional. The sampling technique is random probability sampling of 223 people. The results of the study showed that the p value of the 5 independent variables studied were knowledge (0.000), attitude (0.578), education (0.000), exposure to information (0.000) and support from health workers (0.000) so that it can be concluded that 4 variables have a relationship with BSE behavior, namely knowledge, education, exposure to information and support from health workers. Then the most dominant variable influencing is the variable of exposure to information. The conclusion is that there is a relationship between knowledge, education, exposure to information and support from health workers with SADARI examination in Ujong Patihah Village, Kuala District, Bireuen Regency in 2024.